The Effect of Interest Rates, Economic Growth and Inflation on Profitability in Mining Companies Listed on the Indonesia Stock Exchange - Veronica, Meilin; Sari, Rafika (Universitas Indo Global Mandiri, 2024)
This study aims to analyze the impact of interest rates, economic growth, and inflation on the profitability of mining companies listed on the Indonesia Stock Exchange. Profitability is measured using Return on Assets. (ROA). The data used in this study are secondary data obtained from the company's annual financial statements and macroeconomic data from Bank Indonesia and the Central Statistics Agency (BPS) during the period 2020-2022. The analysis method used is multiple linear regression. The research results indicate that the analysis shows that interest rates have a negative and significant impact on the profitability of mining companies. This is consistent with financial theory, which states that an increase in interest rates raises the cost of capital and reduces company profits. Economic growth has a positive and significant impact on the profitability of mining companies. When the economy grows, the demand for mining products increases, which positively impacts the revenue and profitability of the company. Inflation has a negative but insignificant effect on the profitability of mining companies. Although inflation can increase operational costs, mining companies may be able to offset the impact of inflation through adjustments in product selling prices. Mining companies are expected to manage macroeconomic factors more effectively to enhance their profitability, and the companies should develop risk management strategies, diversification and expansion, cost management in inflationary conditions, and macroeconomic analysis to formulate business strategies that are more adaptive and responsive to changing economic conditions. Keywords: Interest rates, Economic growth, Inflation, Profitability, Mining companies.